1998
DOI: 10.1007/s003359900918
|View full text |Cite
|
Sign up to set email alerts
|

The adipocyte fatty acid-binding protein locus: characterization and association with intramuscular fat content in pigs

Abstract: The porcine A-FABP gene (FABP4) was isolated and sequenced to study the role of A-FABP in the differentiation of intramuscular fat (IMF) accretion in pigs. The coding sequence of the porcine A-FABP gene is highly conserved across human, mouse, and rat. Moreover, all the functionally important amino acids are conserved. This high similarity extends into the first 270 bp of the 5' upstream region. Within this region, a 56-bp nucleotide sequence was completely identical with the corresponding sequence in the mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 24 publications
4
80
1
2
Order By: Relevance
“…No obvious positional candidate locus has so far been identified for FAT1. Gerbens et al [17] localised the adipocyte fatty acid-binding protein (A-FABP) gene on SSC 4 and suggested it might control fat distribution in pigs. Yet, further studies [18] did not support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…No obvious positional candidate locus has so far been identified for FAT1. Gerbens et al [17] localised the adipocyte fatty acid-binding protein (A-FABP) gene on SSC 4 and suggested it might control fat distribution in pigs. Yet, further studies [18] did not support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Genes involved in intracellular fatty-acid transport within skeletal muscles have been also notably proposed. Especially, studies put light on DNA markers or expression levels of FABP4 in pigs (Gerbens et al, 1998 andDamon et al, 2006), cattle Barendse et al, 2009) and avian species (Luo et al, 2006 in chicken;Saez et al, 2008 in ducks) to be associated to variations in IMF content. One study reported a specific allele of the PNAS-4 gene (i.e.…”
Section: Genetic Markersmentioning
confidence: 99%
“…The PCR primers according to Gerbens et al (1998) (F: 5'GGG AAC TCT TGA AGT CTT TCT C, R: 5'GGT ACT TTC TGA TCT AAT GGT G) were used to amplify an approx. 250 bp fragment of the porcine A-FABP gene.…”
Section: Methodsmentioning
confidence: 99%
“…The pig A-FABP gene polymorphism was first described by Gerbens et al (1998). In the first intron three polymorphisms were found, namely a polymorphic microsatellite and two SNPs (single nucleotide polymorphisms), C/T and A/G substitutions occur within the microsatellite sequence.…”
Section: In: Adipocytes (A-fabp) the Liver (L-fabp) Intestine (Ffabmentioning
confidence: 99%
See 1 more Smart Citation